A cost-analysis of complex workplace nutrition education and environmental dietary modification interventions. (December 2017) - Fitzgerald, Sarah; Kirby, Ann; Murphy, Aileen; Geaney, Fiona; Perry, Ivan
Abstract Background The workplace has been identified as a priority setting to positively influence individuals' dietary behaviours. However, a dearth of evidence exists regarding the costs of implementing and delivering workplace dietary interventions. This study aimed to conduct a cost-analysis of workplace nutrition education and environmental dietary modification interventions from an employer's perspective. Methods Cost data were obtained from a workplace dietary intervention trial, the Food Choice at Work Study. Micro-costing methods estimated costs associated with implementing and delivering the interventions for 1 year in four multinational manufacturing workplaces in Cork, Ireland. The workplaces were allocated to one of the following groups: control, nutrition education alone, environmental dietary modification alone and nutrition education and environmental dietary modification combined. A total of 850 employees were recruited across the four workplaces. For comparison purposes, total costs were standardised for 500 employees per workplace. Results The combined intervention reported the highest total costs of €31, 108. The nutrition education intervention reported total costs of €28, 529. Total costs for the environmental dietary modification intervention were €3689. Total costs for the control workplace were zero. The average annual cost per employee was; combined intervention: €62, nutrition education: €57, environmental modification: €7 and control: €0. Nutritionist's time was the main cost contributor across all interventions, (ranging from 53 to 75% of total costs). Conclusions Within multi-component interventions, the relative cost of implementing and delivering nutrition education elements is high compared to environmental modification strategies. A workplace environmental modification strategy added marginal additional cost, relative to the control. Findings will inform employers and public health policy-makers regarding the economic feasibility of implementing and scaling dietary interventions. Trial registration Current Controlled Trials:ISRCTN35108237 . Date of registration: The trial was retrospectively registered on 02/07/2013.